Determinants of the Increase in the Cost of Living in the United States - Kalecki, M. (The Review of Economics and Statistics, 1948)
controls, has found many advocates. The idea of employing OPA methods of price control without rationing would be patently stupid. The establishment of maximum prices which are below free market prices and not coupled with official rationing would create a strong excess demand and would force distribution of the goods to be accomplished through private rationing techniques of retailers favoritism or through first-come-first-served techniques standing in lines or through secret price premiums black markets. Hence, rationing by the government would have to be introduced in order to permit an orderly distribution of the commodities, which would all be scarce at prices fixed below the free market level. In peacetime, without the strong feeling of urgency in the striving for a universally accepted goal, such a system would provide increased incentives to consume the goods, reduced incentives to produce them, increased incentives to break the law, increased incentives to enforce red tape, increased incentives to use arbitrary power and restrict individual freedoms. It would be a disequilibrium system, making shortages and excess demand a chronic condition, without hope for correction and with increasing difficulties of enforcement. It is not intended here to oppose rationing of anything under any circumstances. One may make a plausible argument for resorting even in peacetime to direct controls for a few selected things under very specific circumstances; to wit, (i) if the object of control is a necessity (such as bread, not meat), (2) if the elasticity of its supply in the short run is practically zero, (3 ) if the elasticity of demand for it is very low, and (4) if it can be reasonably and safely expected that the will be over soon, for example, because demand at the controlled price will greatly decrease or supply greatly increase in the very near future. One may conceivably even argue, although less plausibly, for a general price reduction scheme with general rationing if there is evidence that the reduced prices will within a very brief time be the equilibrium prices owing to an imminent decline in demand or increase in supply. No sound argument, however, has thus far been presented to justify direct controls to enforce a general roll back of prices if neither a decline in demand nor an increase in supply is in sight. From this point of view, the United States is not in an emergency expected to pass quickly. We cannot expect a drastic reduction in demand in the near future nor do we wish for it -and production is now at a rate as high as we can possibly maintain.